Collective Representation as a Mobilizer: Race/Ethnicity, Gender, and Their Intersections at the State Level. (June 2016) - Uhlaner, Carole Jean; Scola, Becki
Abstract: Prior research has found that descriptive representation by race, ethnicity, or gender increases political action, but it has paid less attention to how the intersection of these identities influences participation. We extend this literature by assessing the effects on voter turnout of collective descriptive representation in U.S. state legislatures on the basis of race, ethnicity, gender, and their intersections. We argue that members of historically excluded groups respond to the overall composition of their state's legislature. We test this proposition in seven elections (2000, 2002, 2004, 2006, 2008, 2010, and 2012). Our results are consistent with the minority empowerment literature, as overall collective representation does substantially increase turnout among previously excluded groups. However, the impact varies intersectionally. For white women, gender trumps race, as higher collective gender representation, regardless of race or ethnicity, increases voter turnout. For African Americans, race trumps gender, as both black men and women respond most consistently to higher levels of collective racial representation. For Latinos, we find less consistent results, but note a collective ethnic turnout effect for 2002 and 2006. We conclude that collective representation, especially at the intersection of identities, is an important factor influencing levels of turnout among previously excluded groups.